ASSESSING THE BARRIERS OF INITIATION OF INSULIN THERAPY IN INSULIN NAÏVE TYPE 2 DIABETIC PATIENTS IN A TERTIARY CARE HOSPITAL OF KHYBER PAKHTUNKHWA (Journal of Medical & Health Sciences Review, 2025)
Background: The start of insulin treatment in patients with type 2 diabetes who have never used insulin is usually postponed or delayed because of psychological, educational, and social barriers. It is essential to know these barriers in order to be able to get better glycemic control and to prevent the development of complications in the future, especially in areas like Khyber Pakhtunkhwa, where the prevalence of diabetes is ‍‌high.Objective: The objective was to identify the mental health, social and therapy-related obstacles that restrict patients with type 2 diabetes who have never used insulin from starting insulin therapy at a tertiary care ‍‌hospital.Methods: The study aimed to observe a cross-sectional sample, using the Department of Diabetes and Endocrinology at Lady Reading Hospital, Peshawar, in the duration from 9th November, 2024 to 10th May, 2025. In accordance with the WHO sample size estimation, a total of 283 insulin-naïve type 2 diabetic patients were recruited. The data collection involved the use of a well-organised Patient-Reported Outcome (PRO) questionnaire that was specifically developed to identify the misunderstanding and fear of insulin. Both descriptive and inferential statistics were used to analyse the data in SPSS version 26.Results: Some of the significant barriers that were identified are the idea of insulin as a "last resort" treatment, the fear of hypoglycemia, and the fear of injection. Patients with lower education levels had significantly higher barrier scores (p < 0.05). The social stigma and the cost of insulin also led to psychological insulin ‍‌resistance. Conclusion: Several major misconceptions and fears largely contribute to the delay of insulin initiation in patients who have never used insulin. Individually adapted education, better communication, and providing counselling in a culturally appropriate manner are the most important factors in facilitating timely acceptance of insulin and improving the management of ‌diabetes.